Involvement of Acid-Sensing Ion Channel 1b in the Development of Acid-Induced Chronic Muscle Pain - Chang, Chu-Ting; Fong, Sitt Wai; Lee, Cheng-Han; Chuang, Yu-Chia; Lin, Shing-Hong; Chen, Chih-Cheng (Frontiers in Neuroscience, 2019)
Acid-sensing ion channels (ASICs) are important acid sensors involved in neural modulation in the central nervous system and pain-associated tissue acidosis in the peripheral system. Among ASIC subtypes, ASIC1b is the most selectively expressed in peripheral sensory neurons. However, the role of ASIC1b is still elusive in terms of its functions and expression profile. In this study, we probed the role of ASIC1b in acid-induced muscle pain in Asic1b-knockout (Asic1b–/–) and Asic1b-Cre transgenic (Asic1bCre) mice. We tested the effect of ASIC1b knockout in a mouse model of fibromyalgia induced by dual intramuscular acid injections. In this model, a unilateral acid injection to the gastrocnemius muscle induced transient bilateral hyperalgesia in wild-type (Asic1b+/+) but not Asic1b–/– mice; a second acid injection, spaced 1 or 5 days apart, to the same muscle induced chronic hyperalgesia lasting for 4 weeks in Asic1b+/+ mice, but the duration of hyperalgesia was significantly shortened in Asic1b–/– mice. Mambalgin-1, an ASIC1b-containing channel inhibitor that was mixed with acid saline at the first injection, dose-dependently blocked the acid-induced transient and chronic hyperalgesia in Asic1b+/+ mice. In contrast, psalmotoxin 1 (PcTx1), an ASIC1a-selective antagonist, had no effect on acid-induced transient or chronic hyperalgesia. We used whole-cell patch clamp recording to study the properties of acid-induced currents in ASIC1b-expressing dorsal root ganglia (DRG) neurons from Asic1bCre-TdTomato reporter mice. Medium- to large-sized ASIC1b-expressing DRG neurons mainly exhibited an amiloride-sensitive ASIC-like biphasic current (IASIC) in response to acid stimulation, whereas small- to medium-sized ASIC1b-expressing DRG neurons predominantly exhibited an amiloride-insensitive sustained current. Specifically, mambalgin-1 selectively inhibited the IASIC in most ASIC1b-expressing DRG neurons. However, PcTx1 or APETx2 (an ASIC3-selective antagonist) had only a mild inhibitory effect on IASIC in about half of the ASIC1b-expressing DRG neurons. In situ hybridization revealed that ASIC1b-positive DRG neurons co-expressed highly with ASIC1a and ASIC2a mRNA and partially with ASIC3 and ASIC2b. Thus, ASIC1b might form a wide variety of heteromeric channels. ASIC1b-containing heteromeric channels might be promising targets for the therapeutic treatment of acid-induced chronic muscle pain.